Strategi Omnichannel dan Retensi Pelanggan: Analisis pada Industri Ritel Modern Indonesia - Anur Rahmah Tiawulandari; Ikraman; Indah Sofia Ningsih (Journal of Economics, Management, and Accounting, 2026)
This study analyzes omnichannel strategy as an integral component of marketing management in enhancing customer retention within the Indonesian modern retail industry. The acceleration of digital transformation has reshaped consumer purchasing patterns, leading to increased expectations for seamless interactions across physical and digital channels. This research employs a quantitative explanatory approach supported by empirical evidence and official industry data to examine the relationship between omnichannel implementation and customer retention outcomes. The findings indicate that well-integrated omnichannel strategies strengthen customer experience consistency, improve relationship quality, and foster repeat purchase behavior. From a marketing management perspective, omnichannel integration enables firms to optimize the marketing mix, align communication strategies, and manage long-term customer relationships more effectively. These results highlight the strategic importance of managerial coordination across channels in achieving sustainable customer loyalty and maintaining competitiveness in the modern retail sector.